Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian pada Lelang Barang Bekas - Anggraini, Lita Marlen; Defrizal, Defrizal (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of product quality and price on purchasing decisions at used goods auctions. The method in this research uses quantitative methods with a survey approach as the research design. The research population was all auction participants in Bekasi City, totaling 40 auction participants. The sampling technique is a saturated sampling method so that all members of the population are used as samples. Data collection in this research was carried out through the use of a questionnaire. For data analysis, various tests were carried out, including data quality tests (which include validity and reliability tests), classical assumption tests, and the application of multiple linear regression techniques, including the coefficient of determination test. The research results show that simultaneously and partially there is a positive and significant influence on purchasing decisions.